Development of a hybrid technique by integrating electrolysis with sago palm bark activated carbon to treat landfill leachate - Erabee, Iqbal Khalaf (2017)
In this study, a hybrid technique using electrolysis reactor and activated carbon (AC) adsorption was developed in order to decrease organic and inorganic contaminates which are considered important environmental concerns and an important issue to save the water environment. A sample of raw landfill leachate was collected from the Jeram Sanitary Landfill (JSL).The parameters studied were pH, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), total dissolved solids (TDS), electrical conductivity, salinity, turbidity, phosphate, ammonia-nitrogen (NH3-N), nitrate and some heavy metals, e.g. zinc (Zn), copper (Cu), sulphide (S), manganese (Mn) and hexavalent chromium (Cr (VI)). The maximum removal efficiency for TDS, TSS, COD, BOD, salinity, turbidity, Zn and Mn were 78, 82, 94, 87, 82, 87, 87 and 93%, respectively using 60 V electrical potential at contact time (CT) of 120 min. Secondly, the adsorption process using modified AC with potassium permanganate (KMnO4) showed that the removal of these parameters was proportional to the increase of CT (30-360 min) and adsorbent dose of AC (3-10 g/L). The optimum removal efficiencies of TSS, NH3-N, Zn, Cu and sulphide were obtained as being equal to 91, 99 86, 100 and 57%, respectively, at CT of 240 min and 10 g/L adsorbent dose using AC-KMnO4. Two raw materials sago palm bark (SPB) and date pits were utilised as precursors for the preparation of AC by the physicochemical method using activation agents of zinc chloride (ZnCl2), potassium hydroxide (KOH) and sulphuric acid (H2SO4). N2 adsorption-desorption analysis was carried out for porosity characterization of the AC. Thermographimetric (TGA) analysis was also done for the two raw materials. The prepared AC from SPB (AC-SPB) and date pits (AC-DP) showed the maximum surface area of 1737.72 m2/g and 1443.45 m2/g, respectively at 700oC activation temperature. The maximal removal percentages using the dose of 10 mg/L and CT of 180 mins for BOD, COD, NH3-N, Zn and Cr (VI) were 93, 95, 78, 78 and 85%, respectively using the prepared AC-SPB. The morphology of the AC was studied through the scanning electron microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX) patterns. The surface groups present on the AC surface were determined by the Fourier Transform Infrared Spectroscopy (FTIR) analysis. Adsorption isotherms were determined by using Langmuir and Freundlich isotherms. A kinetic study was performed using the pseudo first order and pseudo second order adsorption. The adsorption isotherms of BOD, COD, NH3-N, Zn, and Cr (VI) using the modified AC were well fitted to the Langmuir isotherm. The values of final concentrations of heavy metals (Zn, Mn, Cu, sulphide) are (0.5, 0.17, 0.0, and 0.4 mg/L, respectively) lower than the standards for discharge of leachate required by Department of Environment (DOE, 2010), which equal to (2.0, 0.20, 0.20 and 0.50 mg/L), respectively. Finally, a pilot plant for the treatment of leachate was designed consisting of an electrolysis reactor with a pair of anode electrodes made from aluminum and a pair of cathode electrodes made from iron followed by secondary treatment using the activated carbon adsorption process. The dynamic adsorption behaviour was evaluated using the Thomas, Yoon-Nelson and the Adam’s-Bohart models. The experimental results of the fixed-bed column showed increased removal capacity of NH3-N from 14.33 to 20.81 mg/g. In addition, the Zn and Cr (VI) removal capacities were seen to increase from 7.56 to 8.167 mg/g and 10.5 to 13.23 mg/g, respectively.